Analisis Putusan Hakim Terhadap Penolakan Dispensasi Kawin Perspektif Maslahah Mursalah - Dwi Yoga Pratama; Waluyo Sudarmaji; Najih Abqori (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to analyze the judge's decision regarding the rejection of a marriage dispensation in case number 340/Pdt.P/2024/PA.Wsb., using the perspective of maslahah mursalah. The research focuses on the judge's considerations in rejecting the marriage dispensation request and how this decision can be viewed from the perspective of maslahah (public welfare) that is not explicitly regulated in legal texts, but takes into account the general benefit. The method used in this study is a qualitative approach with document analysis, studying court rulings and examining the concept of maslahah mursalah in Islamic jurisprudence related to the protection of individuals and society. The results of the study indicate that the judge in case number 340/Pdt.P/2024/PA.Wsb. rejected the marriage dispensation request because there was no urgent reason to marry a child under 19, even though the child was pregnant. This rejection was based on the Marriage Law and the principle of maslahah mursalah, which prioritizes the protection of individual rights and the welfare of society. The decision aims to protect the child’s rights, avoid long-term harm, and maintain social structure by ensuring that marriage occurs at a mature age, physically, psychologically, and sociali.